2015
DOI: 10.1093/fampra/cmv004
|View full text |Cite
|
Sign up to set email alerts
|

Direct-access to abdominal ultrasonic investigation from general practice--the role in earlier cancer diagnosis

Abstract: The findings in this study might indicate that GPs refer patients assessed to have a higher risk of cancer through direct-access US. The finding was statistically non-significant, and further research is required to confirm this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…Of 1278 patients referred to the NSSC-CPP pathway by their general practitioners (GPs), a cross-sectional study reported that 16% of patients were diagnosed with cancer. 13 The most common symptoms recorded were weight loss (53%), fatigue (50%) and pain (37%). The most common clinical findings were ‘affected general condition’ (36%), GP ‘gut feeling’ (23%) and abnormal abdominal examination (13%).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer was diagnosed across a broad range of 18 subgroups, the most common of which were lung (18%), colorectal (13%), haematological (10%), pancreatic (9%) and upper gastrointestinal (8%). 13 A later cohort study including 938 patients referred to the NSSC-CPP reported that 35% were diagnosed with serious disease within 3 months, of which one-third had cancer. 14 …”
Section: Introductionmentioning
confidence: 99%
“…[304][305][306] In Denmark, the diagnostic interval has shortened signifi cantly, and direct access to investigations has been appropriately used. 303,307 Progress can also be made by technological innovation in point-of-care testing and detailed clinical audit studies. However, any system making referrals that are contingent on the presence of symptoms with high positive predictive values risks delays in the diagnosis of those with less specifi c symptoms.…”
mentioning
confidence: 99%